2014
DOI: 10.3389/fgene.2014.00139
|View full text |Cite
|
Sign up to set email alerts
|

Identification of developmentally-specific kinotypes and mechanisms of Varroa mite resistance through whole-organism, kinome analysis of honeybee

Abstract: Recent investigations associate Varroa destructor (Mesostigmata: Varroidae) parasitism and its associated pathogens and agricultural pesticides with negative effects on colony health, resulting in sporadic global declines in domestic honeybee (Apis mellifera) populations. These events have motivated efforts to develop research tools that can offer insight into the causes of declining bee health as well as identify biomarkers to guide breeding programs. Here we report the development of a bee-specific peptide a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 46 publications
0
43
0
Order By: Relevance
“…A detailed description of the selection of the two contrasting colonies, the tolerant (S88) and the susceptible (G4), selected from a large diverse gene pool (approximately 50 000 colonies), is given in Robertson et al . (). The varroa infestation rates in white‐eyed and dark‐eyed pupae in sealed broods (n = 500) of G4 were 88 and 70%, respectively, and the rate in the adults was 67 mites per hundred bees.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A detailed description of the selection of the two contrasting colonies, the tolerant (S88) and the susceptible (G4), selected from a large diverse gene pool (approximately 50 000 colonies), is given in Robertson et al . (). The varroa infestation rates in white‐eyed and dark‐eyed pupae in sealed broods (n = 500) of G4 were 88 and 70%, respectively, and the rate in the adults was 67 mites per hundred bees.…”
Section: Resultsmentioning
confidence: 99%
“…A complementary study on the same colony phenotypes using kinome arrays showed that varroa mite resistance and susceptibility are also reflected at the signal transduction level (Robertson et al ., ). Distinct kinome profiles were observed between G4 and S88 bees at three developmental stages (pink‐eyed, dark‐eyed and adult).…”
Section: Discussionmentioning
confidence: 97%
“…As opposed to clinical medicine, custommade array designs are much more common in this field, for instance peptide arrays containing bovine peptides have been successfully employed to identify novel drug targets to combat Jone's disease, a granulomatous affliction of the intestine that affects cattle [40][41][42]. Likewise chicken-specific [43], Syrian hamster-specific [13], and even honey bee-specific [44] platforms have been employed to generate specific insight into questions related to veterinary medicine. The results obtained in this field suggest that remarkably species-specific kinotypes appear to exist, supporting the use of custom species-specific peptide arrays [45].…”
Section: Peptide Arraying Remains Dominant For Kinome Profilingmentioning
confidence: 99%
“…Novel tools to identify specific molecular signatures of parasite and pathogen resistance, such as bee-specific peptide array which characterizes and correlates phosphorylated protein profiles with Varroa resistance [67 ], should be developed and incorporated into breeding efforts. Varroa resistance may be conferred not only by increasing hygienic behavior but also by increased resistance to the specific viruses it vectors [68] thus highlighting the need to identify resistance-associated QTLs.…”
Section: Future Directionsmentioning
confidence: 99%